2015
DOI: 10.1080/15321819.2015.1132229
|View full text |Cite
|
Sign up to set email alerts
|

An Easy and Useful Noninvasive Score Based on α-1-acid Glycoprotein and C-Reactive Protein for Diagnosis of Patients with Hepatocellular Carcinoma Associated with Hepatitis C Virus Infection

Abstract: This study aimed to evaluate the diagnostic value of α-1-acid glycoprotein (AGP) and C-reactive protein (CRP) and develop a predictive score to improve the diagnosis of hepatocellular carcinoma (HCC). AGP and CRP were measured in serum of 53 HCC patients and 20 liver cirrhosis (LC) patients, in addition to 15 healthy individuals. Area under receiver-operating characteristic curves (AUCs) was used to create a predictive score comprising AGP, CRP, alpha fetoprotein, and albumin. The diagnostic performances of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Eighteen articles that met the inclusion criteria of our study conducted on the relationship between hepatitis B and hepatitis C and CRP were included in the study. Eleven studies were associated with hepatitis B (2, 7, 15-23) and seven were associated with hepatitis C (1,(9)(10)(11)(12)(13)(14). Table 1 and summarize the pooled mean level, lower limit, upper limit, I 2 , and P value of CRP associated with hepatitis B and hepatitis C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen articles that met the inclusion criteria of our study conducted on the relationship between hepatitis B and hepatitis C and CRP were included in the study. Eleven studies were associated with hepatitis B (2, 7, 15-23) and seven were associated with hepatitis C (1,(9)(10)(11)(12)(13)(14). Table 1 and summarize the pooled mean level, lower limit, upper limit, I 2 , and P value of CRP associated with hepatitis B and hepatitis C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is used to determine the progression and development of the disease inflammatory markers. CRP has been shown to be significantly altered in viral hepatitis (1,2,7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Studies freely accessible in PubMed or ScienceDirect on hepatitis patients between January 1, 2015, and December 31, 2019, were reviewed that are displayed in Figures 1A and B and 2A and B analyzed by the random-effects model.…”
Section: Selection Of Test Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of AFP and Desgamma-carboxyprothrombin yields an AUC of 0.846 [30]. Omran et al reported that the combination of acid glycoprotein, albumin, C reactive protein, and AFP has an AUC of 0.92 and a sensitivity of 85% [31]. According to Attallah et al, combining cytokeratin-1 and nuclear protein-52 with AFP provides an AUC, sensitivity, and specificity of 0.90, 80%, and 92%, respectively, for identifying HCC [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because evidence has established that ORM is associated with carcinogenesis and behavior in many organs, changes in the ORM serum level in HCC have been investigated as diagnostic markers. The results of many studies have indicated that the ORM level is increased in patients with HCC and is significantly higher than that in patients with chronic hepatitis and cirrhosis[ 34 - 37 ]. ORM has also been shown to improve HCC diagnostic performance when combined with other markers, such as des-g-carboxy prothrombin (DCP)[ 38 ].…”
Section: Orm In Liver Tumorsmentioning
confidence: 99%